Fujairah, United Arab Emirates. Archaeological investigations at the site of Dibba 76: Late Bronze Age – Iron Age multiple tombs and their buried individuals. Season 2017 - Pfeiffer, Kristina; Petiti, Emmanuele; Reichmuth, Silvio; Ruben, Isabelle (e-Forschungsberichte des DAI, 2018)
In spring 2017 a second field season at the Emirate of Fujairah was carried out in the frame of the continuation of the cooperation between the Fujairah Tourism & Antiquities Authority and the Orient Department of the DAI. The field season focused on excavations of two Late Bronze – Iron Age multiple burials at the site of Dibba 76.